2017
DOI: 10.1186/s12913-017-2563-y
|View full text |Cite
|
Sign up to set email alerts
|

Few opportunities to influence decisions regarding the care and treatment of an older hospitalized family member: a qualitative study among family members

Abstract: BackgroundThe drive towards patient involvement in health services has been increasingly promoted. The World Health Organisation emphasizes the family’s perspective in comprehensive care. Internationally there is an increased emphasis on what patients and their family tell about the hospital experiences. However, current literature does not adequately address the question of participation experiences among relatives of older hospitalized family members. There is a paucity of research with a generational perspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 38 publications
1
6
0
Order By: Relevance
“…Informants reported that such information from close relatives was particularly important if the older adult was previously unknown to the care teams or was cognitively impaired. This supports studies demonstrating a shift towards patient and family involvement (Lin and Fagerlin 2014 ; Lindhardt et al 2008 ; Nyborg et al 2017 ) including a recent systematic review on older adults admitted to hospital emphasizing close relatives’ important role in providing information as it often gets lost in the transfer to hospital (Pulst et al 2019 ). These previous studies have, however, not considered the potential risks of inequity including the impact of not having close relatives.…”
Section: Discussionsupporting
confidence: 72%
“…Informants reported that such information from close relatives was particularly important if the older adult was previously unknown to the care teams or was cognitively impaired. This supports studies demonstrating a shift towards patient and family involvement (Lin and Fagerlin 2014 ; Lindhardt et al 2008 ; Nyborg et al 2017 ) including a recent systematic review on older adults admitted to hospital emphasizing close relatives’ important role in providing information as it often gets lost in the transfer to hospital (Pulst et al 2019 ). These previous studies have, however, not considered the potential risks of inequity including the impact of not having close relatives.…”
Section: Discussionsupporting
confidence: 72%
“…The first author, who did not know any of the relatives in advance, conducted all interviews between June and November 2020. A semi‐structured interview guide with open‐ended questions was developed, inspired by previous research about the interaction between relatives of older hospital‐admitted patients and HCPs (Bragstad et al, 2014 ; Dyrstad, Laugaland, et al, 2015 ; Lindhardt et al, 2006 ; Mackie et al, 2019 ; Nyborg et al, 2017 ; Stein‐Parbury et al, 2015 ). The focus during the interview was relatives’ experiences of the admission, including experiences of their contact with the HCPs (e.g., communication and information received).…”
Section: Methodsmentioning
confidence: 99%
“…Studies published before the COVID-19 pandemic have demonstrated that relatives to older acutely admitted patients play a vital role in the patient's treatment and care (Bragstad et al, 2014;Dyrstad, Laugaland, et al, 2015;Nyborg et al, 2017;Sagoo & Grytnes, 2020;Stein-Parbury et al, 2015;Storm et al, 2014).…”
Section: Backg Rou N Dmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies primarily report on experiences of family caregivers' involvement in the care for hospitalized older persons based on qualitative studies. These studies indicated that family caregivers find their ability to influence decisions seriously reduced when an older person is admitted to the hospital (Lowson et al., 2013 ; Nyborg et al., 2017 ). These caregivers did not always feel acknowledged as competent care partner by professionals (Aasbø et al., 2017 ; Lindhardt et al., 2006 ) and experienced an insufficient exchange of information and knowledge about disease related aspects, care and support (Bove et al., 2016 ; Røthing et al., 2015 ).…”
Section: Introductionmentioning
confidence: 99%